Research on the Course Teaching Reform of Advanced Application of Databases (Asian Education Studies, 2022)
Advanced application of databases is a comprehensive new curriculum involving computer science, mathematics, informatics and management. Students are required to master more database-related knowledge. It cultivates students' database programming ability. However, as far as the current arrangement of advanced application courses for the database in undergraduate colleges and universities is concerned, the practical content of some schools is still relatively backward. This paper mainly aims at the problems existing in the practical teaching of the advanced application course of the database, and puts forward specific suggestions for improvement and corresponding measures.